Color transparency of Daniel M. Singer and Luigi G. Silvestri (1975)
"Color transparency of Daniel M. Singer (1930-) and Luigi G. Silvestri at the 1975 Asilomar Conference. The Asilomar Conference on Recombinant DNA was an influential conference, organized by Paul Berg (1926-2023), that considered the potential biohazards of, and need to regulate, biotechnology. It was held in February 1975 at the Asilomar Conference Grounds in Pacific Grove, California. The conference was a milestone in the history of science, marking the beginning of attempts to study the social implications of scientific progress and to mitigate against negative social impact."
Keywords: California--Pacific Grove--Asilomar Conference Grounds; Congresses and conventions; Biology--Congresses; Recombinant DNA--Congresses; Silvestri, Luigi G.; Singer, Daniel M., 1930-